Strategic Analysis of Business Decisions PT Flextronics Techology Indonesia by Utilizing Generative Artificial Intelligence (GenAI) in the Electronics Manufacturing - Aklani, Syaeful Anas; Basiron, Halizah; Zulkarnain, Nur Zareen (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
New technologies in manufacturing companies continue to develop and innovate, companies face increasing challenges related to operational efficiency, supply chain complexity, and the need for continuous innovation. PT Flextronics Technology Indonesia, as one of the large-scale industries in the Batam city, is trying to overcome this challenge by integrating Generative Artificial Intelligence (GenAI) into its strategic decision making. GenAI, a transformative part of artificial intelligence, offers unmatched capabilities in generating insights, optimizing processes, and driving innovation.  This research carries out a comprehensive strategic analysis of PT Flextronics Technology Indonesia's decision by evaluating the potential impact of using GenAI in all main operational domains such as management, engineering and quality. Using a mixed-methods approach, this research combines qualitative insights from stakeholder interviews and surveys with quantitative analysis of pilot projects to assess the feasibility and benefits of Gen AI integration. The findings highlight that GenAI significantly improves decision-making accuracy, reduces operational costs, and drives innovation in product design and production processes. However, successful implementation requires addressing challenges such as workforce readiness, data security, and initial investment costs. The study also emphasizes the importance of aligning GenAI initiatives with organizational goals and encouraging stakeholder engagement to ensure continued adoption. This research provides actionable insights and a roadmap for PT Flextronics Technology Indonesia utilizes GenAI as a strategic tool, strengthening its position as a leader in the electronics manufacturing sector while setting a benchmark for future AI-based industrial transformation.